Increasing important roles of child and adolescent psychiatrists in the treatment of gaming disorder: Current status in Japan - Tateno, Masaru; Matsuzaki, Takanobu; Takano, Ayumi; Higuchi, Susumu (Frontiers in Psychiatry, 2022)
Background Digital gaming is the most common leisure activity among children and adolescents in Japan, especially in males. Playing online gaming has become more common among school-age children over the years. As a result, excessive online gaming in younger children has become a significant social problem in Japan. Previous studies have demonstrated that excessive online gaming could cause various mental health issues in children and adolescents. At medical institutions having child and adolescent psychiatry services, there is an increasing number of children and adolescents with various problems related to excessive gaming. The aim of this study was to investigate the current practice of gaming disorder (GD) in clinical settings in Japan. Methods The subjects of this study were all of 414 child and adolescent psychiatrists certified by the Japanese Society for Child and Adolescent Psychiatry (JSCAP). The study questionnaire was mailed to all subjects from the official secretariat of JSCAP. Study subjects were requested to answer the questionnaire anonymously. The survey contained three types of responses: open responses; single and multiple-choice responses; and, responses on a five-point Likert scale. The questionnaire consisted of 14 questions regarding GD. Results We received 159 responses. The most common reason for a visit to child and adolescent psychiatry service which results in a subsequent diagnosis of GD was school refusal/absenteeism followed by disruption of sleep-awake rhythm. The most common specialized treatment for GD currently offered at child and adolescent psychiatry service is individual psychotherapy. The two most frequently experienced difficulties in the treatment of GD were low motivation to achieve recovery and a large variety of combined problems other than excessive gaming itself. With regard to the three most common psychiatric comorbidities of GD, they were autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and depression. Discussion The results of our survey revealed that although GD is a behavioral addiction, many children and adolescents with GD first visit child and adolescent psychiatry clinics rather than specialized clinics for addiction which are usually designed and staffed for adult patients. Because it is known that GD is more prevalent among young males, including junior high and high school students, GD has become one of the most important clinical issues in child and adolescent psychiatry today. The important roles of child and adolescent psychiatrists in the treatment of GD has been increasing.